A Note on Credit Spread Forwards - HERTRICH, Markus (Journal of Advanced Studies in Finance, 2016)
This note presents the most commonly used definition of credit spread forwards, discusses two alternative definitions and proposes one of these three definitions as the standardized version that should be used in the future to prevent confusion. In addition, this note gives an overview on the definition of this credit derivative contract in the most relevant hand-and textbooks in banking and credit risk management that include topics on credit derivatives. It also exemplifies by means of one textbook that although being a standard textbook in banking and financial institutions management for years and read by thousands of practitioners and students, there are still books that erroneously mix definitions, which motivates the present note.
Keywords: academic education, banking, credit derivative, credit spread forward, financial institutions management, hedging